La devolución parcial del saldo a favor del IGV como incentivo fiscal para fomentar el desarrollo de las industrias alternativas a la fabricación de bolsas de plástico y de recipientes o envases descartables. Análisis - Chaupis Rojas, Mary Del Pilar (2022)
Law No. 30884 approved the regulatory framework on single-use plastics, other nonreusable plastics, and disposable expanded polystyrene (Styrofoam) containers or packagings to be used for food and beverages for human consumption in Peruvian territory. Said law sets out, among other provisions, the creation of a tax on the consumption of plastic bags as well as the progressive prohibition of specific commercial activities related to the manufacturing and commercialization of single-use plastics and disposable containers or packagings, and allows the creation of tax incentives to promote: i) the use of technologies and supplies such as biopolymers and other similar compostable and nonpolluting materials of animal or vegetal origin; and ii) the normal development of the activities performed by micro and small entrepreneurs faced with the gradual reduction of polymer bags and expanded polystyrene products. Thus, throughout this research, we have analyzed and developed tax measures whose purpose is to promote the development of alternative industries to the manufacturing of plastic bags and disposable containers or packagings, in order to meet the demand and contribute to the protection of the right of every person to live in a balanced and adequate environment for their development, as such right is protected by item 22 of Article 2 of the Political Constitution of Peru. Finally, we have carried out and developed a legal-technical evaluation for the creation of a tax incentive aimed at micro and small entrepreneurs engaged in the manufacturing of alternatives to plastic bags and disposable containers or packagings.